Hepatoprotective Effect of Pancha Lavana Dravagam Against Paracetamol induced Hepatotoxicity in Wistar Albino Rats - An in-Vivo Study - G. Kaaruniya; A. Mariappan; V. Suba; R. Meenakumari (International Journal of Ayurveda and Pharma Research, 2021)
Objective: To evaluate the liver protective effect of Pancha Lavana Dravagam (PLD) against Paracetamol induced hepatotoxicity in wistar albino rat models. Methods: The hepatoprotective activity of PLD was evaluated using paracetamol induced liver damage in rats. Wistar albino rats were divided into five groups of six animals each. Paracetamol 1gm/kg bw, p.o. was given to produce liver toxicity. The normal control was given the vehicle (water 1ml/kg bw, p.o). Two test groups with PLD 1ml/kg, 2ml/kg bw, p.o. were tested for hepatoprotective potential. Silymarin 50mg/kg bw, p.o. was given as standard drug. All these drugs were administered for 7 days. On 8th day, the animals were sacrificed and blood was collected from retro-orbital plexus and analyzed for serum enzymes like Serum Glutamate Pyruvate Transaminase (SGPT), Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Alanine Phosphate (ALP), Total Bilirubin, Total Proteins and liver was excised for histopathological analysis. Results: In toxicant control group, paracetamol produced liver toxicity due to decrease in glutathione (GSH) by oxidative stress and mitochondrial dysfunction of hepatic cells. It resulted in an increase of serum liver enzymes like SGPT, SGOT, ALP and Total Bilirubin. This increased serum liver enzymes were reduced significantly in the test drug PLD treated groups and Standard group. The histology of liver tissues was also improved in PLD treated groups when compared to the toxicant group. Conclusion: Since, no scientific evidence is available to claim the hepatoprotective effect of PLD, in vivo studies were conducted. It demonstrated that it has a potent hepatoprotective effect against the paracetamol induced hepatotoxicity by suppression of the reactive oxygen species and increasing the anti-oxidant glutathione in liver cells.